Analisis Komparatif Daya Saing Ekspor Besi dan Baja Belgia dan Tiongkok di Pasar Mesir dalam Perspektif EPD, dan ECI - Ananda Marda Fitria; Naora Yolla Greshinta; Fahrizal Taufiqqurrachman (INDO PUBLISHING, 2026)
The iron and steel industry plays a strategic role in supporting industrial development and infrastructure expansion in developing countries, including Egypt as one of the major importers in the Middle East and North Africa (MENA) region. In the context of increasing global competition, exporting countries are required to possess strong competitiveness and adaptive export structures. This study aims to comparatively analyze the export competitiveness of iron and steel products from Belgium and China in the Egyptian market. The analytical approaches employed include Export Product Dynamics (EPD) to identify export growth positioning and Economic Complexity Index (ECI) to capture the level of economic sophistication of exporting countries. This research uses secondary data derived from international trade databases over a specific period. The results indicate that China demonstrates stronger export dynamics and market expansion in the Egyptian market, while Belgium shows relatively higher product sophistication but more limited market penetration. These findings suggest that competitiveness in iron and steel exports is not only influenced by economic complexity, but also by scale efficiency and export market responsiveness.